WELCOMING THE SEMICONDUCTOR INDUSTRY IN GHANA: CHALLENGES AND RECOMMENDATIONS – A CASE STUDY - GIDEON ADOM-BAMFI; DANIEL OPOKU; BENJAMIN KOMMEY (Journal of Engineering Studies and Research)
The Semiconductor Industry is one industry that has been driving technological innovations for decades since its birth in the USA. Semiconductors form the building blocks of a wide array of consumer, medical and industrial electronics. The growth of many economies in the world can be attributed to the growth in the semiconductor industry in such countries. The global semiconductor industry consists of companies in the USA, South Korea, Taiwan, China, and the European Union. However, the semiconductor industry has no presence in the African region, in Ghana to be specific. This work investigates some challenges associated with the establishment of the semiconductor industry in Ghana, including challenges from basic research and development to manufacturing and marketing. The paper also highlights some recommendations which are key in laying the foundation for the entry of the industry in Ghana, including the provision of tax incentives, training of personnel, etc.